2015
DOI: 10.1016/j.seizure.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Bitemporal epilepsy: A specific anatomo-electro-clinical phenotype in the temporal lobe epilepsy spectrum

Abstract: The possibility of recognising BTLE patients during pre-surgical evaluation or being able to suspect bitemporal seizures before VEEG by identifying particular anatomo-electro-clinical patterns is diagnostically important for epileptologists and can help to prevent possible surgical failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
(62 reference statements)
5
32
0
Order By: Relevance
“…Fourth, widespread abnormalities in white matter found in our study might have been the result of unilateral or bilateral TLE. However, we could not distinguish the 2 conditions, although both diseases are associated with different underlying networks . Future studies are needed to investigate how the 2 conditions (unilateral TLE vs bilateral TLE) may affect widespread brain regions differently.…”
Section: Discussionmentioning
confidence: 79%
“…Fourth, widespread abnormalities in white matter found in our study might have been the result of unilateral or bilateral TLE. However, we could not distinguish the 2 conditions, although both diseases are associated with different underlying networks . Future studies are needed to investigate how the 2 conditions (unilateral TLE vs bilateral TLE) may affect widespread brain regions differently.…”
Section: Discussionmentioning
confidence: 79%
“…When the laterality of the EZ has not been determined, bilateral electrode recordings are likely easier with SEEG electrodes given that they can be implanted bilaterally without repositioning or performing a bilateral craniotomy. SEEG has been used with success for the characterization of the EZ in patients with bitemporal epilepsy [40][41][42], obviating the need for bilateral craniotomies or burr holes that would be required with SDEs. At centers using SDEs, bilateral craniotomies can be avoided by using bilateral burr holes with implantation of strip electrodes, bilaterally.…”
Section: Seeg and Sde Techniquementioning
confidence: 99%
“…Patients with BHS are an ignored group in epileptology despite their increased burden related to the bilateral hippocampal involvement and there is only a small body of literature on this group and related characteristics. 5,[8][9][10][11]22 We showed that history of FSE, mental retardation, status epilepticus, psychosis, slowing of the EEG background activity were significant clues for BHS patients in comparison to UHS group.…”
Section: Discussionmentioning
confidence: 86%
“…8 However, there were no consecutive series investigating these interesting associations in BHS versus unilateral HS (UHS) in the same study with comparative design. Recently Didato et al 9 retrospectively investigated characteristics of 48 patients with bilateral TLE in comparison with 38 patients with unilateral TLE and found that bilateral TLE cohort was significantly older at the time of epilepsy onset, showed frequent bilateral asynchronous interictal epileptiform discharges, bilateral upper limb dystonia, and less recognizable initial ictal EEG discharges. But their cohort also included patients, with lateral TLE, many other etiologies and only 39.6% of their bilateral group had HS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation